Time-resolved in situ XANES study of the redox properties of Ce0.9Zr0.1O2 mixed oxides - Zimicz, Maria Genoveva (2012)
The aim of this paper is to gain further insight in the reduction and reoxidation processes taking place when Ce0.9Zr0.1O2 mixed oxides are in reducing or oxidizing atmospheres, respectively. The reduction process of these mixed oxides synthesized by two stoichiometric nitrate-aminoacid gel-combustion routes using glycine and lysine as fuels is studied by conventional H2-Temperature Programmed Reduction experiments. The results are compared with those obtained by time-resolved in situ X-ray absorption near-edge spectroscopy (XANES) in the energy level corresponding to the Ce LIII absorption edge. The reoxidation process by this last technique is also studied. Even though the identical composition and crystal structure of both samples, the redox processes resulted very different for each solid, suggesting the influence of specific surface area, pore volume and particle size on them.